Exercise and fitness in the age of social distancing during the COVID-19 pandemic - Nyenhuis, S. M.; Greiwe, J.; Zeiger, J. S.; Nanda, A.; Cooke, A. (Journal of Allergy and Clinical Immunology, 2020)
The US Physical Activity Guidelines recommend that all adults, even those with chronic medical conditions, should engage in at least 150 minutes to 300 minutes a week of moderate-intensity exercise, if they are able. New data are emerging that exercise may reduce the risk of acute respiratory distress syndrome, a major cause of death in patients with coronavirus disease 2019 (COVID-19). As health care providers, we need to consider what can we recommend to our patients to stay physically active during this time of social distancing and how to maintain fitness regimens that began during the stay-at-home period.